Catalytic behavior of Ru nanoparticles supported on carbon fibers for the ethanol steam reforming reaction - Bosko, María Laura (2018)
Ru catalysts on carbon fibers were prepared by electroless deposition, with 0.6 wt% Ru loading. The reduced and used catalysts were characterized by different techniques in order to analyze oxidation states and surface composition, the metallic content at volumetric level, and particle size. These solids were evaluated for the production of hydrogen via ethanol steam reforming at different gas hour space velocities (GHSV) at 723 K. Space velocity significantly influenced the distribution of products favoring the formation of acetaldehyde at short contact times while, for longer times, it was possible to obtain a hydrogen rich stream, free of oxygenate compounds.